Effect of replacing fish-meal by soybean on digestibility, protein and minerals utilization in growing piglets - KUMAR, ASHOK; THAKUR, S; SRIVASTAVA, J P; SINGH, S K (The Indian Journal of Animal Sciences, 2013)
The present study was carried OUt on grcwing piglets maintained at the pig farm of university. Concentrate mixture T1 (6.5% fish-meal), T2 (fish-meal was completely replaced by pressure- cooked crushed soybean), and T3 (T2 supplemented with lysine and methionine @ 10 g/100 kg of feed) were used. The daily DM intake varied but differences were nonsignificant. The digestibility coefficient of DM, CP, EE, CF, NFE and OM in various groups also did not differ significantly. This shows that digestibility of soybean and its various nutrients was higher than that of fish-meal. DCP, DE and ME of ration varied from 16.3 to 16.8%,3.4 to 3.5 Mcal/kg and 2.8 to 2.9 Mcal/kg in different groups, respectively. Balance of N, Ca and P were positive in all the 3 groups, The Nand Ca-retention varied from l3.9 to 16.2 g and 2.8 to 4.3. g/day, the difference within groups being nonsignificant. However, the P-retention was significantly lower in TI (1.5 g/ day) as compared T2 (3.2 g/day).